Using the Administration to Update and Evaluate Urban Planning for Cities - et. al., Hadeel Mowafaaq Mahmood , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The planning process takes place to face a number of challenges and obstacles that address and continue for a long time to form a plan that includes the fundamental changes in society and keep pace with population and urban growth, and planning and the formation of blueprints is a basis to meet the needs of society, but the passage of time to configure it to keep pace with growth and the speed of increasing population and technical growth, it requires research studies Faster to configure a re-planning of plans and studies as an alternative to re-planning and supporting them with follow-up and continuous evaluation processes that are among the basic components of management operations, which is the solution to reduce problems and shortcomings and support for planning processes as a current and long-term treatment The role of management is important to support the planning process in the presence of evaluation and follow-up to meet the requirements of the city and its expansion Urban development and development, and looking forward to the most prominent concepts and ways that decision-makers take with techniques and methods that make the city and the services provided to it in the best image that makes the city with urban development and urban management represented by the countries.